2022
DOI: 10.9734/ijpss/2022/v34i2231413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soil Mixtures on Early Growth Performance of Grevillea robusta and Cupressus lusitanica Seedlings in the Highlands of Kenya

Abstract: Seedling production nurseries have been receiving much attention because of increasing demand for seedlings. In sub-Saharan Africa studies have showed over 50% of smallholder seedlings planted were sourced in tree nurseries. This has caused a rise in need to improve quality of seedlings especially focused on production level. The focus on most studies on early growth performance of selected key species important either for commercial plantation or agroforestry has been varied on length of the study periods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Recent studies by [24], confirms that Cupressus lusitanica performed better than Grevillea robusta in different soil mixtures although this was not done in these study. Earlier work by [25] stated that the effect of pot sizes on seedling growth depend on the type of species to be grown which corroborates with the findings of this study, in that the two species showed different growth characteristics. The findings by [26], showed that species of plants responds differently to container size with regards to biomass distribution.…”
Section: Effect Of Varying Pot Sizes On Shoot Growth and Leaf Number ...supporting
confidence: 92%
“…Recent studies by [24], confirms that Cupressus lusitanica performed better than Grevillea robusta in different soil mixtures although this was not done in these study. Earlier work by [25] stated that the effect of pot sizes on seedling growth depend on the type of species to be grown which corroborates with the findings of this study, in that the two species showed different growth characteristics. The findings by [26], showed that species of plants responds differently to container size with regards to biomass distribution.…”
Section: Effect Of Varying Pot Sizes On Shoot Growth and Leaf Number ...supporting
confidence: 92%